2016
DOI: 10.1063/1.4943025
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of hydrogen plasma in a microwave plasma chemical vapor deposition reactor

Abstract: The aim of this work is to build a numerical model of hydrogen plasma inside a microwave plasma chemical vapor deposition system. This model will help in understanding and optimizing the conditions for the growth of carbon nanostructures. A 2D axisymmetric model of the system is implemented using the finite element high frequency Maxwell solver and the heat transfer solver in COMSOL Multiphysics. The system is modeled to study variation in parameters with reactor geometry, microwave power, and gas pressure. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 34 publications
3
24
1
Order By: Relevance
“…As shown in Figure. 6, increasing the microwave power from 340 to 580 W, as the pressure is increased simultaneously increases the H 2 rotational temperatures from 930 to 1340 K. This result is explained by two interdependent simultaneous effects: (i) because the gas temperature depends on the energy transferred from the electric field to the gas molecules by electrons during collisions, increasing the plasma power increases the gas temperature; (ii) increasing the pressure increases the collision frequency in the plasma and then the energy transfer between electrons and gas molecules. These results are in good agreement with the OES measurements suggested that the gas temperature has weak dependence on power and very strong dependence on pressure [77]. Rotational energy, E J' (cm -1 ) Figure 6.…”
Section: A Experimental Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…As shown in Figure. 6, increasing the microwave power from 340 to 580 W, as the pressure is increased simultaneously increases the H 2 rotational temperatures from 930 to 1340 K. This result is explained by two interdependent simultaneous effects: (i) because the gas temperature depends on the energy transferred from the electric field to the gas molecules by electrons during collisions, increasing the plasma power increases the gas temperature; (ii) increasing the pressure increases the collision frequency in the plasma and then the energy transfer between electrons and gas molecules. These results are in good agreement with the OES measurements suggested that the gas temperature has weak dependence on power and very strong dependence on pressure [77]. Rotational energy, E J' (cm -1 ) Figure 6.…”
Section: A Experimental Resultssupporting
confidence: 89%
“…Since atoms, ions and molecules create a unique emission spectrum specific to each element, OES enables their identification. OES has the advantage of being noninvasive and has already been used to monitor the state of plasma in situ and to determine the concentration of the species and different plasma parameters, such as the electron densities and temperatures of diamond [85][86][87][88][89][90][91][92][93], carbon nanotubes [94] and, more recently, graphene [77]. Since an important step in achieving control of defect-free and few-layers graphene synthesis involves understanding the role of plasma properties, OES can help to identify the species responsible for graphene growth.…”
Section: B Plasma Optical Emission Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations
“…The rotational temperatures of normalN2+(BX) and normalH2true(normald3normalΠunormala3normalΣg+true) were extracted from their emission spectra and interpreted as the gas temperature in the plasma, as shown in Figure c. A Boltzmann plot is used to derive the rotational temperatures of these two species . In the center region of the plasma, H 2 has a relatively higher emission intensity and lacks perturbation from other rotational lines, making it a clearer signal for determining the temperature.…”
Section: Resultsmentioning
confidence: 99%